Molecular Regulation of NK Cell Maturation - Bi, Jiacheng; Wang, Xuefu (Frontiers in Immunology, 2020)
Natural killer (NK) cells are innate lymphocytes specialized in immune surveillance against tumors and infections. To reach their optimal functional status, NK cells must undergo a process of maturation from immature to mature NK cells. Genetically modified mice, as well as in vivo and in vitro NK cell differentiation assays, have begun to reveal the landscape of the regulatory network involved in NK cell maturation, in which a balance of cytokine signaling pathways leads to an optimal coordination of transcription factor activity. An increased understanding of NK cell maturation will greatly promote the development and application of NK cell-based clinical therapy. Thus, in this review, we summarize the dynamics of NK cell maturation, describe recently identified factors involved in the regulation of the NK cell maturation process, including cytokines and transcription factors, and discuss the importance of NK cell maturation in health and disease.